Prognostic Significance of PD-L1 Expression In Patients With Primary Oropharyngeal Squamous Cell Carcinoma: A Meta-Analysis - Polesel, Jerry; Menegaldo, Anna; Tirelli, Giancarlo; Giacomarra, Vittorio; Guerrieri, Roberto; Baboci, Lorena; Casarotto, Mariateresa; Lupato, Valentina; Fanetti, Giuseppe; Boscolo-Rizzo, Paolo; Fratta, Elisabetta (Frontiers in Oncology, 2021)
Background: At present, the prognostic significance of programmed cell death receptor ligand 1 (PD-L1) expression in oropharyngeal squamous cell carcinoma (OPSCC) patients is still controversial. In this study, we aim to synthesize relevant studies that have assessed the prognostic value of PD-L1 in patients with primary OPSCC treated according to the current standard-of-care. Methods: A systematic search of Medline/PubMed, Cochrane, Embase, Web of Science, and Scopus was conducted to define the prognostic role of PD-L1 expression in OPSCC. All studies published before July 31, 2021 were screened. Summary hazard ratios (sHR) with 95% confidence intervals (CIs) were calculated using a random-effects model. Results: A total of 1522 OPSCC patients from 12 studies were included. PD-L1 expression in OPSCC tumor cells (TCs) was significantly associated with longer overall survival (sHR=0.63, 95% CI 0.50-0.79), and progression-free survival (sHR=0.62, 95% CI 0.49-0.79). A benefit in survival was also observed in PD-L1-positive OPSCC patients who underwent surgery (sHR=0.34, 95% CI 0.18-0.65). Finally, although PD-L1-positive expression was related to better outcomes both in HPV-negative and HPV-positive OPSCC, the difference reached the statistical significance only in the HPV-positive subgroup (sHR=0.37, 95% CI 0.19-0.73). No heterogeneity emerged between studies for all considered outcomes, with I2 ranging from 0% for progression-free survival to 11% for overall survival. Conclusions: PD-L1 expression on TCs associated with improved survival in OPSCC. In particular, HPV-positive OPSCC most benefited from PD-L1 expression when compared to the PD-L1 negative counterpart. Thus, PD-L1 might represent a useful biomarker to stratify prognosis in OPSCC in addition to HPV status.